Volatile composition, antioxidant activity, and antioxidant components in saffron cultivated in Turkey. (18th December 2017) - Kosar, M.; Demirci, B.; Goger, F.; Kara, I.; Baser, K.H.C.
ABSTRACT: Oven dried cut stigmas of Crocus sativus L. cultivated in Eskisehir and Safranbolu regions of Turkey were subjected to micro distillation to extract steam volatiles. They were then analysed by Gas Chromatography and Gas Chromatography/Mass Spectrometry, simultaneously. The colour compounds were extracted with 80% methanol and analysed by High Pressure Liquid Chromatography HPLC/DAD and HPLC/MS/MS. The activities of the extracts of saffron against 2, 2ʹ-azinobis-3-ethylbenzothiazoline-6-sulphonic acid free radical (ABTS ●+ ) were investigated using on-line (HPLC-ABTS ●+ ) and off-line methods. Safranal (62.1 and 49.3%) and α-isophorone (10.0 and 16.3%) were found as the characteristic aromatic volatiles in the Eskisehir and Safranbolu samples, respectively. Crude saffron extracts showed high total antioxidant activity against ABTS ●+ radical.